Pengembangan Desa Wisata Perkebunan Teh Jamus di Desa Girikerto Kecamatan Sine Kabupaten Ngawi - Lestari, Aprillia Audry; Winarti; Suhita, Damayanti (Solidaritas, 2024)
Tourism village development is a process that forces ways to develop or advance touristvillages. One of the tourist villages that implements village development as a tourist attractionis the jamus tea plantation in Girikerto Village which is analyzed using four indicatorsaccording to. Cooper (2015:159) which consists of Attraction, Accessibility, Amenity(Supporting Facilities) and Ancillary (Supporting Institutions).The aim of this research is todescribe the development of the Tourism Village in Girikerto village so that it can attracttourists. This research uses a descriptive method with a qualitative approach with datacollection techniques, namely observation, interviews and documentation. The data analysistechniques used are data condensation, data presentation and drawing conclusions.The resultsof this research show that at the Jamus Tea Plantation a deer breeding area was built andthere is a new photo spot vehicle called the sky ladder photo spot. 1) In terms of cleanlinessattractiveness indicators that still need to be improved. 2) In terms of accessibility indicators,the road to the Jamus Tea Plantation is damaged and has not yet been repaired, but signs forthe road to the tourist attraction have been provided. 3) In the amenity indicators at the JamusTea Plantation in 2023, accommodation and cafes will begin to be developed. However, whatis hampering the availability of facilities at the Jamus Tea Garden is the lack of funding. As aresult, parking facilities are inadequate. 4) In additional indicators at the Jamus TeaPlantation, there are no youth organizations and pokdarwis